Mergers and acquisitions: A qualitative study in the medical device sector - Alon Ben Jacob (International Journal of Management, Economics and Social Sciences (IJMESS), 2020)
One of the key processes that business leaders are using to grow their organizations is mergers and acquisitions (M&A). As such, the M&As are considered as a critical process with considerable implications for the company's profitability and growth. Still, between 70 to 90 percent of the M&As deals fail to deliver the expected value to the acquirers. The purpose of this qualitative study was to explore strategies that industry leaders used to conduct successful M&A processes. The conceptual framework of this study is based on Sarasvathy's effectuation theory. Eight face-to-face interviews were conducted with participants from a global healthcare company who acted as the company's presidents or executives and had experience conducting M&As. The data were coded, and themes were emerged using Microsoft Office and NVivo 10 software. Six themes were emerged through data analysis: leadership focus, value creation, integration strategy, the review process, relationship development, and organizational governance. The results of this study could be used to improve leadership strategies when conducting the process of M&A. The implications for positive social change might enhance the stability of the healthcare industry and the individuals who consume healthcare products. Also, this will bring to improved health outcomes, well-being, longevity, and quality of life.
Keywords: G30; G32; G34; 330; Mergers; acquisitions; effectuation theory; entrepreneur; integration; inorganic growth; new product development